Diagnostic value ultrasound signs of stones less than or equal to 10 mm and clinico-radiological variants of ureteric colic - Denis V. Krakhotkin; Volodymyr A. Chernylovskyi; Kemal Sarica; Arman Tsaturyan; Evangelos Liatsikos; Jurijus Makevicius; Nikolay Yu Iglovikov; Dmitry N. Pikhovkin (Asian Journal of Urology)
Objective: To determine the diagnostic value of ultrasound signs of urinary stones less than or equal to 10 mm and to determine clinico-radiological variants of ureteric colic. Methods: A total of 455 ultrasound investigations were performed in patients referring to emergency department with urolithiasis and symptoms suspected of ureteric colic between January 2021 and May 2021. In addition to microscopic evaluation of urine sediment to detect different crystals and non-contrast spiral computed tomography to detect stones, B-mode and color Doppler sonography was performed to assess the presence of acoustic shadow (AS) and twinkle artifacts (TA) as possible signs of stone(s) in ureter. Results: While the sensitivity and specificity of AS and TA were higher than 90% in patients with stones greater than 5 mm; positive prognostic values of these parameters were found to be extremely low for stones with sizes of 1–3 mm with specificity and sensitivity values not exceeding 53%. The sensitivity and specificity of AS and TA in the upper and lower ureters were higher for stones greater than or equal to 5 than for compared to those less than 5 mm. At the same time, the diagnostic values of TA and AS for middle ureter stones were very limited. The most prevalent clinico-radiological variants of ureteric colic were types I, III, and V being observed in 39%, 28% and 21% cases, respectively. Conclusion: Our results demonstrate that TA and AS parameters seem to have a very low sensitivity and specificity in the diagnosis of urinary stones less than 5 mm. The diagnostic value of TA and AS increase significantly in stones greater than or equal to 5 mm. Therefore, clinicians need to be very careful for overestimating the diagnostic values of TA and AS for stones less than 5 mm and non-contrast spiral computed tomography must be the method of choice for patients presenting to emergency department with ureteric colic.